Android-based Voice of Insomnia Implementation for Elderly Sleep Quality: A Literature Review - Suhaiba; Sukihananto (STIKes Al-Ma'arif Baturaja, 2024)
Elderly people who experience sleep disturbances result in deterioration of disease conditions, fatigue, weakness, increased risk of falls, psychological disorders, and decreased quality of life. Poor sleep patterns trigger insomnia events such as difficulty maintaining sleep. The use of technology has been widely used in overcoming the problem of sleep disorders, one of the implementations used by the Voice of Insomnia application is an android-based application as a relaxation music therapy to overcome sleep disorders or insomnia and is expected to reduce the use of drugs as a stimulus by people with insomnia. The purpose of this literature review is to explore the benefits of implementing the Voice of insomnia application on the quality of elderly sleep. the method used in this literature review is a systematic study by collecting and analyzing relevant literature related to the research topic. Academic journals were searched through online databases such as science direct, Scopus, Google Scholar, Pubmed, Clinicalkey Nursing from 2015 to 2023. The results of literature review from several journals provide information on the benefits of using android-based technology, especially in people with insomnia as an alternative option to improve the quality of elderly sleep. Interventions using android-based technology can improve sleep quality and reduce the incidence of insomnia in the elderly. Voice of Insomnia application as an android application in the form of relaxation music therapy for people with sleep disorders or insomnia. Furthermore, the application of android-based technology can be used as a non-invasive mobile therapy media to help maintain sleep quality.